2016
DOI: 10.1038/srep24419
|View full text |Cite
|
Sign up to set email alerts
|

Human oropharynx as natural reservoir of Streptobacillus hongkongensis

Abstract: Recently, we reported the isolation of Streptobacillus hongkongensis sp. nov. from patients with quinsy or septic arthritis. In this study, we developed a PCR sequencing test after sulfamethoxazole/trimethoprim and nalidixic acid enrichment for detection of S. hongkongensis. During a three-month study period, among the throat swabs from 132 patients with acute pharyngitis and 264 controls, PCR and DNA sequencing confirmed that S. hongkongensis and S. hongkongensis-like bacteria were detected in 16 patients and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…According to the author Lau et al (21), Streptobacillus hongkongensis is a novel bacterial species that permanently found in human oropharynx and there might be more other…”
Section: Resultsmentioning
confidence: 99%
“…According to the author Lau et al (21), Streptobacillus hongkongensis is a novel bacterial species that permanently found in human oropharynx and there might be more other…”
Section: Resultsmentioning
confidence: 99%
“…Differential abundance testing of bacterial communities based on nicotine dependence scores revealed a relative abundance of Streptobacillus hongkongensis among more nicotine dependent smokers (high Fagerström score). Previous studies reported the isolation of S. hongkongensis from patients with quinsy, pneumonia, and septic arthritis [34,35], which was later reported as part of the human oropharynx natural reservoir [36]. Increased risk of developing serious respiratory illnesses might be partly attributed to more nicotine dependent smokers.…”
Section: Discussionmentioning
confidence: 99%
“…Differential abundance testing of bacterial communities based on nicotine dependence scores revealed a relative abundance of Streptobacillus hongkongensis among more nicotine dependent smokers (high Fagerström score). Previous studies reported the isolation of S. hongkongensis from patients with quinsy, pneumonia, and septic arthritis [36,37], which was later reported as part of the human oropharynx natural reservoir [38]. Increased risk of developing serious respiratory illnesses might be partly attributed to more nicotine dependent smokers.…”
Section: Discussionmentioning
confidence: 99%